Budidaya Hidroponik Pakcoy (Brassica Rapa L) dan Ikan Nila dengan Sistem Aquaponik (Studi Kasus Desa Losari Nganjuk) - Amos Hosea P; Dioz Ananditya P; Ernik Ernawati; Nungki Regata A; Salma Dwi Z (Pusat Riset dan Inovasi Nasional, 2023)
Aquaponics is a combined system of fish farming techniques and hydroponic plant cultivation. Fish manure and feed residues are very dependent on the supply of nutrients in the aquaponic system of red tilapia (Oreochromis niloticus) aquaculture. The level of production of vegetable crops in a certain area is also influenced by the total nutrient input ratio of feed to domestic fish per day. The aquaponic system utilizes optimum water supply for each commodity by utilizing a recirculation system. The type of fish used is fish that live in freshwater, a type of tilapia. Fish farming includes the maintenance of fish, which pays attention to the growth and development of fish. Hydroponics itself is a way of farming without using soil as a medium but using water which contains controlled nutrients containing the essential elements needed for plant growth. The location of this research was conducted in Losari Village, Kec. Gondang, Kab. sleepy. It aims to increase the demand for vegetables, limited land and space, efficiency in land use, and decoration. In addition, this cultivation system allows for increased production of cultivated products with limited land and water sources, and creates its own beauty. (9 pt).